EFFECT OF BRAIN BASED LEARNING STRATEGIES ON CREATIVE THINKING OF MIDDLE LEVEL STUDENTS - Saloni; Kulshrestha, Arun Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the present research study, to examine the effect of brain-based learning strategies on creative thinking of class VIIth science students. The researcher has used experimental research method and pre-test post-test two group design for her research. The research study was conducted on a sample of 60 students of class VIIth of S.D. Inter College, Agra city (U.P) which is selected by purposive sampling method. The students were randomly divided into two groups experimental and control groups by simple random sampling method. The experimental group was taught through brain-based learning strategies while the control group was taught through traditional method. For Statistical analysis researcher has been used mean, median, t-test. The findings of the research revealed that the students of the experimental group performed better for creative thinking, while the students of the control group performed very low for creative thinking. Brain-based learning strategies are an effective method of teaching in science for middle level students.